Association between the dietary inflammatory index and infertility: a systematic review and meta-analysis - Zahedi, Yasamin; Bonyanpour, Shayan; Alizadeh, Seyed Danial; Ravankhah, Sarah; Zare, Alireza; Izadi, Bahareh; Apelian, Shant; Sekhavati, Eghbal; Tabrizi, Reza (Frontiers in Nutrition, 2025)
IntroductionTo evaluate the association between the dietary inflammatory index (DII) and risk of infertility in human participants.MethodsA comprehensive search was conducted using the Scopus, PubMed, Web of Science, Cochrane, Embase, and Google Scholar databases until January 2025. All observational studies that reported an association between the DII and infertility in human participants were included. Data were extracted on study characteristics, DII scores, and infertility outcomes. Meta-analyses were conducted using random-effects models, and the heterogeneity of studies was evaluated using I2 statistics.ResultsOf the 801 studies screened, nine met the inclusion criteria, involving 17,711 individuals. The analysis revealed a significant association between a pro-inflammatory diet (characterized by high DII scores) and infertility (odds ratio (OR): 1.61, 95% CI: 1.32–1.95) among participants in the highest quartile of the DII. Additionally, each unit increase in the DII was associated with a 10% higher risk of infertility (OR, 1.10; 95% CI: 1.05–1.15). Subgroup analyses revealed a significant association between anti-inflammatory diets (low DII scores) and infertility in men and increased infertility risk in both the Iranian and US populations and in female participants on a pro-inflammatory diet. The sensitivity analysis indicated that the overall OR remained stable, with the results not being significantly influenced by the exclusion of individual studies.ConclusionThese findings highlight the potential role of inflammation-related dietary factors in reproductive health and suggest that dietary modifications targeting inflammation could be a promising intervention for infertility management. Further randomized controlled trials are needed to confirm these findings and to establish causal relationships.Systematic review registrationThis systematic review is registered in PROSPERO with code: CRD42024567145. URL: https://www.crd.york.ac.uk/PROSPERO/view/CRD42024567145.